PENERAPAN SISTEM MERIT MENUJU PEMERINTAHAN YANG TERPERCAYA - MEISI KALESARAN (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
Abstract The purpose of this research is to find out the implementation and strategy of the North Sulawesi Provincial Government to implement the merit system and to formulate the supporting factors and inhibiting factors during the implementation of the merit system. researchers will use descriptive research methods with a qualitative approach. The research data taken in this study are primary data in the form of data from interviews and observations. While secondary data in the form of data sources such as BPS, books, reports, journals, and others are available via the internet and taken directly at the research site, namely the Regional Personnel Agency of North Sulawesi Province. The implementation of the merit system at the Regional Personnel Board of North Sulawesi province is divided into several indicators in accordance with Government Regulation Number 11 of 2017 concerning ASN Management. All indicators related to the merit system in this regulation are in accordance with the merit system principle proposed by researchers in the theory used according to Shafritz, et al. Keyword: Regional Civil Service Agency, Trustworthy Government, Merit System